Physical activity interventions in early life aimed at reducing later risk of obesity and related non‐communicable diseases: A rapid review of systematic reviews. (16th August 2019) - Reilly, John J.; Hughes, Adrienne R.; Gillespie, Jennifer; Malden, Stephen; Martin, Anne
Summary: To identify useful components of interventions aimed at prevention of childhood obesity and related non‐communicable diseases (NCDs), which included physical activity and which targeted any or all of four life‐course stages: peri‐conception; pregnancy; infancy and toddlerhood (0 to 23 months); and early childhood (24 to 59 months). In May 2016, WHO Geneva searched the Cochrane Library and PubMed for systematic reviews of interventions including physical activity to prevent childhood obesity or risk factors for obesity‐related NCDs. Using a narrative synthesis, the efficacy of randomized controlled trials (RCTs) to alter energy balance outcomes (measures of weight status or body fatness) was characterized by life‐course stage, study characteristics, intervention functions (as defined in the behaviour change wheel), and level of the socio‐ecological model (SEM) targeted. The quality of included systematic reviews was assessed. We retrieved 82 reviews from the World Health Organization (WHO) search, of which 23 were eligible for the present synthesis. The number of eligible studies by life‐course stage was: 0 (peri‐conception); 0 (pregnancy); 8 (infancy and toddlerhood, age 0 to 23 months; seven RCTs; age); and 37 (early childhood, age 24 to 59 months; 30 RCTs;). Thus, there was a lack of evidence for physical activity interventions during peri‐conception and pregnancy. Almost all relevant studies in the 0‐ to 23‐ and 24‐ to 59‐month life‐course stages were multicomponent interventions (ie, targeted physical activity, dietary, and/or sedentary behaviours). Interventions with evidence of efficacy tended to target multiple levels of the SEM, with emphasis on parents, and extend over long periods. Effective intervention elements for early life obesity prevention included classes on parenting skills, alteration of the kindergarten playground, and financial incentives. Evidence from low‐ and middle‐income countries was scarce, and evidence for intervention effect on obesity‐related NCDs was missing. Future physical activity interventions in toddlerhood and early childhood aimed at prevention of obesity should adopt the characteristics typical of effective interventions identified by the present synthesis. There is an urgent need for more evidence on physical activity interventions set in low‐ and middle‐income countries and which target the peri‐conception and pregnancy periods.